ANALYSIS OF THE EFFECT OF THE LIQUIDITY RATIO ON FINANCIAL PERFORMANCE IN. MULTI BINTANG INDONESIA TBK - Desi Wulan Sari; Siswohadi (Sekolah tinggi ilmu ekonomi pemuda, 2021)
This study is to determine how the influence of financial performance is based on the current ratio and how the influence of financial performance is based on the quick ratio and how the influence of financial performance is based on cash ratios at PT Multi Bintang Indonesia Tbk. The data used are secondary in the form of financial reports for the period 2016 to 2019. The population is in the form of financial reports of PT Multi Bintang Indonesia Tbk. The sample used is probability sampling. The data collection technique used is the documentation method in the financial statements of PT Multi Bintang Indonesia Tbk. The data analysis techniques used were a normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression test, and performed with the help of the computer program SPSS version 17.0 for Windows. The method used to assess the financial performance of PT Multi Bintang Indonesia Tbk is the liquidity ratio. The results of this study indicate that the current ratio and cash ratio do not have a significant effect on financial performance and the quick ratio has no significant effect on financial performance. Partially the current ratio and cash ratio are not proven to significantly affect the dependent variable (financial performance) and the quick ratio has no significant effect on financial performance. Simultaneously, the current ratio, cash ratio, and quick ratio have not been able to pay short-term obligations. This is because one of the components of current debt shows a large nominal level, compared to changes in current assets that affect the amount of current debt that is greater than current assets.